Similarity Test Among Several Accessions of Mutant (M4) Cayenne Pepper(Capsicum frutescens L.) Based on Fruit Qualitative Character - Makhziah, Makhziah; Soedjarwo, Djarwatiningsih P; Khairunissa, Asya Zhafira (Plantropica: Journal of Agricultural Science, 2025)
Cayenne pepper (Capsicum frutescens L.) is one of Indonesia's leading horticultural commodities. The decline in cayenne pepper production does not match the increasing level of consumer demand. Gamma-ray irradiation-induced mutations are one of the methods used in plant breeding to increase genetic diversity and develop new superior varieties. Cayenne pepper plants exposed to gamma-ray irradiation undergo character changes, resulting in mutant accession populations with diverse characteristics. A similarity test of mutant accessions is conducted to determine the genetic distance between accessions and their parents. This study aims to identify accessions with the greatest genetic distance to obtain good candidate parents for crossing. The research was conducted at the Faculty of Agriculture, National Development University 'Veteran' East Java. The experimental design used was a Randomized Block Design (RBD) with five replications and one factor, namely, 10 mutant cayenne pepper (M4) accessions or lines resulting from gamma-ray irradiation-induced mutations. The results of the similarity test in the form of a dendrogram show that the 10 mutant accessions, along with their parents and comparisons, exhibited a similarity coefficient range of 56% to 92%. The lowest similarity coefficient is found in accessions AU4 and AU8, which is 56%. Accessions AU4 and AU8 have the furthest genetic distance from accession AU9, and these accessions have the potential as parental candidates in future crossings to produce offspring with enhanced traits and diversity.